Tips for Conducting a Gender Analysis at the Activity or Project Level - and Cozzarelli, Cathy (USAID, 2010)
I. What is gender analysis? II. Relevant sections of the ADS III. Process – What should you do to collect the information you need to conduct a gender analysis at the activity or project level? IV. What questions should you ask in the context of doing your gender analysis? - Access - Knowledge, Beliefs, and Perceptions - Practices and Participation - Time and Space - Legal Rights and Status - Power and Decision-making IV. What should you do after you ask these questions?